Data Balancing Approach Using Combine Sampling on Sentiment Analysis With K-Nearest Neighbor - Kondy, Evlyn Pricilia; Siswanto, Siswanto; Ilyas, Nirwan (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
One of the topics that has been discussed on twitter is the rules regarding the removal of masks. However, there's a chance that the data from Twitter contains unequal data classes. An unequal amount of data can cause the classification process to malfunction. Combining under- and oversampling techniques is known as combine sampling, and it is a data-balancing strategy. The research's data consists of Indonesian tweets using the hashtag